Trends in Flexible Sensing Technology in Smart Wearable Mechanisms–Materials–Applications - Sen Wang; Haorui Zhai; Qiang Zhang; Xueling Hu; Yujiao Li; Xin Xiong; Ruhong Ma; Jianlei Wang; Ying Chang; Lixin Wu (Nanomaterials)
Flexible sensors are revolutionizing our lives as a key component of intelligent wearables. Their pliability, stretchability, and diverse designs enable foldable and portable devices while enhancing comfort and convenience. Advances in materials science have provided numerous options for creating flexible sensors. The core of their application in areas like electronic skin, health medical monitoring, motion monitoring, and human–computer interaction is selecting materials that optimize sensor performance in weight, elasticity, comfort, and flexibility. This article focuses on flexible sensors, analyzing their “sensing mechanisms–materials–applications” framework. It explores their development trajectory, material characteristics, and contributions in various domains such as electronic skin, health medical monitoring, and human–computer interaction. The article concludes by summarizing current research achievements and discussing future challenges and opportunities. Flexible sensors are expected to continue expanding into new fields, driving the evolution of smart wearables and contributing to the intelligent development of society.